Microbiology : fundamentals and applications - Atlas, Ronald M. (New York : Macmillan Publishing Company, 1984)
The book is intended to be comprehensive and to meet the varied teaching needs of different institutions.
Section One. Background to the study of microbiology -- Section Two. Microbial anatomy -- Section Three. Microbial metabolism -- Section Four. Microbial genetics -- Section Five. Microbial growth -- Section Six. Microbial taxonomy.
Includes bibliographical references and index.
Keywords: MICROORGANISMS